ENZYME SYSTEMS FROM THE THERMOPHILIC FUNGUS TALAROMYCES EMERSONII FOR SUGAR BEET BIOCONVERSION - Sara Fernandes (BioResources, 2008)
The thermostable enzyme systems produced by the thermophilic ascomycete fungus Talaromyces emersonii cultivated on various carbon sources were investigated for the production of high value products from sugar beet. A broad range of enzymatic activities relevant to cellulose, hemicellulose, and pectin hydrolysis were identified in T. emersonii culture filtrates. In hydrolysis experiments conducted at 71ºC, the enzyme cocktails generated sugar-rich syrups from untreated sugar beet plants. Maximal levels of sugar beet hydrolysis were obtained with T. emersonii enzyme cocktails induced with sorghum/ beet pulp (68%) and sugar beet plant (56%). The principle monosaccharides released were glucose, xylose, and arabinose with minor amounts of galactose and galacturonic acid. Northern analysis of RNA isolated from T. emersonii when sugar beet plants were used as the sole carbon inducing source showed that genes required for polysaccharide hydrolysis and five carbon monosaccharide metabolism were co-ordinately expressed.